2018
DOI: 10.1371/journal.pone.0204817
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of bambara groundnut (Vigna subterranea (L.) Verdc.) for sustainable food and nutrition security in semi-arid regions of Zimbabwe

Abstract: Bambara groundnut (Vigna subterranea (L.) Verdc.) is an indigenous legume crop, cultivated by subsistence farmers throughout sub-Saharan countries. Research findings indicate that the crop has great nutritional and agronomic potential, but it remains scientifically neglected. A baseline study was conducted in seven districts in semi-arid regions of rural Zimbabwe to gather knowledge on current production and utilization of bambara groundnut, assess its role in providing sustainable food and nutrition security … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 45 publications
3
67
1
Order By: Relevance
“…It is grown widely in sub-Saharan Africa and is also present at low levels in Thailand, Malaysia, and Indonesia ( 7 ). Higher preference for Bambara groundnut has been observed in dry regions prone to drought ( 14 ). This is possibly linked to its ability to produce reasonable yields under such conditions, hence acting as a safety net for farmers.…”
Section: Closing the Food Supply Gap Through Improved Production Of Bmentioning
confidence: 99%
“…It is grown widely in sub-Saharan Africa and is also present at low levels in Thailand, Malaysia, and Indonesia ( 7 ). Higher preference for Bambara groundnut has been observed in dry regions prone to drought ( 14 ). This is possibly linked to its ability to produce reasonable yields under such conditions, hence acting as a safety net for farmers.…”
Section: Closing the Food Supply Gap Through Improved Production Of Bmentioning
confidence: 99%
“…For Bambara groundnut, trade is often confined to the immediate village boundaries, with little commercialization or processing involved [31,32], and negative traditional beliefs are associated with the crop in parts of Africa (e.g., [33] for Malawi). However, few studies have specifically examined issues of marketing for Bambara groundnut [19,34,35] and little information is available on its value chain in Mali. Similarly, for fonio, most of the studies looking at Mali only focus on specific actors along the value chain in a specific location (e.g., [15] or [36] for urban consumers of fonio in Bamako).…”
Section: Introductionmentioning
confidence: 99%
“…Through a survey in Zimbabwe [237] and previous reports [70], soaking and or roasting prior to milling of BG into grits and flour were disclosed as pretreatment methods to circumvent the HTC and HTM problem. BG grits take approximately 45 min of boiling prior to consumption, equaling boiling time of freshly harvested BG pods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to limited firewood supply and the long time required for boiling, consumption of BG is hampered [76], thus warranting the need for alternative processing methods [70]. A recent survey performed by our group Mubaiwa, Fogliano [237], revealed that soaking and or roasting are applied by some households as pretreatment methods prior to milling of BG seeds into flour in an effort to circumvent the HTC problem (Fig 6.1). In previous studies, soaking [28], germination [209] and roasting are also employed to bypass the HTM phenomenon.…”
Section: Introductionmentioning
confidence: 99%